Análise de influência para o Modelo de Regressão de Valor Extremo sob Censura do tipo II - Carvalho, Victor José Araujo de Carvalho (2016)
In this work, we will analyze the problem of evaluating the Influence of observations in the Extreme Value Regression model under Censure type II. Such a model is very important in the analysis of lifetime data. First, we obtain the log-likelihood function, score function, and the information matrix. Then we will now discuss some methods of influence, such as global influence and local influence. In the local influence analysis we will derive expressions for normal bends under different disturbances schemes. Finalize obtaining a closed-form expression for the overall leverage.